2013
DOI: 10.1007/s11136-013-0568-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in overweight and obese children and adolescents: a literature review

Abstract: Identifying variables associated with lower QOL in obese children and adolescents offers new perspectives for prevention and care. Further research is needed to better elucidate these findings. Better understanding QOL is a key element essential for the treatment for childhood and adolescent obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

28
197
3
26

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(254 citation statements)
references
References 68 publications
28
197
3
26
Order By: Relevance
“…Specific physical health risks experienced by children with overweight and obesity may include apnea, musculoskeletal problems, asthma, diabetes, and/or sleep problems (Ranzenhofer et al, in press). Psychosocial risks to children and adolescents with overweight and obesity may include internalizing and externalizing problems, self-esteem, peer-related problems, and/or diminished health-related quality of life (HRQoL; Eremis et al, 2004;Buttitta et al, 2014). Though previous studies and reviews have suggested that evidence-based interventions to reduce BMI can be associated with improved HRQoL (e.g., Tsiros et al 2009), no studies were identified that quantitatively evaluated the associations between change in adiposity and change in HRQoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific physical health risks experienced by children with overweight and obesity may include apnea, musculoskeletal problems, asthma, diabetes, and/or sleep problems (Ranzenhofer et al, in press). Psychosocial risks to children and adolescents with overweight and obesity may include internalizing and externalizing problems, self-esteem, peer-related problems, and/or diminished health-related quality of life (HRQoL; Eremis et al, 2004;Buttitta et al, 2014). Though previous studies and reviews have suggested that evidence-based interventions to reduce BMI can be associated with improved HRQoL (e.g., Tsiros et al 2009), no studies were identified that quantitatively evaluated the associations between change in adiposity and change in HRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…Such results are consistent with a well-developed literature indicating that children with context of physical health (Centers for Disease Control and Prevention, 2011). obesity are at particular risk for compromised HRQoL (e.g., Buttitta, Iliescu, Rousseau, & Guerrien, 2014;Griffiths et al, 2010;Schwimmer, Burwinkle, & Varni, 2003;Tsiros et al, 2009). Indeed, analyzing published data from a number of studies in the literature, Tsiros et al reported an inverse linear relationship between body mass index (BMI) and HRQoL for both child self-reported (r=-0.70, p<0.01) and parent proxy-reported (r=-0.77, p<0.01) child HRQoL.…”
mentioning
confidence: 99%
“…QOL assesses physical ability, psychological well-being, social interactions and school or work performance domains. 6 Quality of life is defined as overall well-being 7,15 described by objective indicators and subjective evaluation of physical, material, social, productive, emotional and civic wellbeing. It can be seen as a multidimensional construct that reflects one's self-perceptions of enjoyment, satisfaction with life 8 and general health.…”
Section: Introductionmentioning
confidence: 99%
“…Worryingly, the majority of these medical concerns have traditionally only presented in adults [2,4] and as Reilly and Kelly (2011) reviewed, a large body of evidence now confirms obesity in childhood and adolescence can lead to premature mortality and physical morbidity in later life [2]. The psychopathology of obesity in young people is a concern with overweight and obese children experiencing poor quality of life, lower self-esteem [5,6] and an enhanced risk of being socially isolated than their healthy weight counterparts [7]. Several variables are associated with low Quality of life, QOL, such as self-image, bullying, bodily pain, quality of food intake, physical activity, screen time, parents, and weight status [6].…”
Section: Introductionmentioning
confidence: 99%
“…The psychopathology of obesity in young people is a concern with overweight and obese children experiencing poor quality of life, lower self-esteem [5,6] and an enhanced risk of being socially isolated than their healthy weight counterparts [7]. Several variables are associated with low Quality of life, QOL, such as self-image, bullying, bodily pain, quality of food intake, physical activity, screen time, parents, and weight status [6]. Being obese in childhood is also associated with depressive symptoms and thoughts of suicide, often linked to bullying in schools and/or through the use of social media networks [8,9].…”
Section: Introductionmentioning
confidence: 99%